Comparison of Healing Rates Between Giving Meniran Leaf Extract (Phyllanthus niruri) and Topical Antibiotics for Cuts on the Backs of White Wistar Rats (Rattus Norvegicus) - Sigalingging, Yulia Emma Wahyu Kristi A. B.; Tarigan , Antje Irmella; Thomson Nadapdap (Jurnal EduHealth, 2023)
Antibiotic or wound-covering gel might be used to expedite wound healing, especially incisions. The research compares healing rates of cuts on the backs of Wistar strain white rats (Rattus norvegicus) treated with meniran leaf extract (Phyllanthus niruri) and topical antibiotics. Antibiotics and meniran leaf extract (Phyllanthus niruri) are independent variables in this laboratory experiment. The dependent variable Macroscopic photographs, show the fastest wound healing without infection or allergies. The research was done in the University of North Sumatra Faculty of Mathematics and Natural Sciences lab. Rat Acclimatization, Meniran Leaf Extract and Cream Formula, White Rat Incision, Histopathological Observation, and Data Processing comprise the research method. SPSS 22 analyzes research. Shapiro-Wilk determines data normalcy. For well-distributed data, one-way ANOVA calculated group mean differences (P > 0.05). The Post Hockey test (HSD) showed treatment differences (P 0.05). The Kruskal-Walli test tests irregular data. The study indicated that the average healing rate for cuts in the negative control group (K-) was considerably different from K+, treatment groups P1, P2, and P3. This is because the negative control group (K-) lacks active chemicals that speed wound healing. The 15% meniran leaf extract gel group healed white mice and cut injuries better than the 5% and 10% green betel leaf extract gel groups. The group administered antibiotic cream (K+) was similar to that given 15% meniran leaf extract gel at 15%.